The French University in perdition: an account of forty years of neoliberal ideology at the helm (1979-2020). Testimony from other latitudes - Blanchet, Philippe (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
The paper narrates the unfolding of neoliberal policies in the last decades of the French higher education system. It offers an autobiographical account of the impact that such policies have had on teaching and research to identify those elements that have contributed to the gradual precarization of academic work and those which have had a broader impact on segregating the social body. The paper highlights specific acts of resistance that are intertwined with broader political struggles and identifies the legal milestones of the neoliberal policies.
Keywords: University; Public Service Mission; Academic Freedom; Neoliberalism; Public Management; Precarious working